2004
DOI: 10.1038/sj.bmt.1704688
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia and syndrome of inappropriate antidiuretic hormone secretion complicating stem cell transplantation

Abstract: Summary:Hyponatremia is a common electrolyte disorder in hospitalized patients. Although there are a few case reports of hyponatremia following stem cell transplantation (SCT), no reports concerning the incidence are currently available. We describe the occurrence of hyponatremia and the syndrome of inappropriate secretion of antidiuretic hormone (SIADH) following SCT. In a single center analysis of 140 patients, hyponatremia and SIADH were observed in 40 and 11.4% of patients, respectively, following SCT. Ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…3 In this study, although this conclusion was confirmed (data not shown), neurological sequelae following SCT occurred in survivors with SIADH more frequently than in those without SIADH. All patients with SIADH were promptly and appropriately treated with fluid restriction, diuretics or hypertonic saline (3% NaCl) and recovered from hyponatremia.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…3 In this study, although this conclusion was confirmed (data not shown), neurological sequelae following SCT occurred in survivors with SIADH more frequently than in those without SIADH. All patients with SIADH were promptly and appropriately treated with fluid restriction, diuretics or hypertonic saline (3% NaCl) and recovered from hyponatremia.…”
Section: Discussioncontrasting
confidence: 50%
“…These results, except for age, concurred with our previous report. 3 Although we have no available data at present, IL-6 has been reported to be involved in SIADH. [12][13][14] In addition, levels of cytokines such as IL-6 and tumor necrosis factor-a are known to be high in SCT from an HLA-mismatched donor or an unrelated donor.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In approximately half of these cases, hyponatremia develops due to syndrome of inappropriate antidiuretic hormone ( ADH ) secretion (SIADH) (1,2). The general causes of SIADH include central nervous system infection (3), malignancies, such as leukemia and lymphoma (4), and drugs, such as chemotherapeutics and antiepileptic agents (5).…”
Section: Introductionmentioning
confidence: 99%